PRAKTIK DINASTI POLITIK PADA PEMILIHAN KEPALA DAERAH KOTA TANGERANG SELATAN TAHUN 2020 (Studi Kasus Pasangan Benyamin Davnie dan Pilar Saga Ichsan) - Ahmad Aryo Zidane, (2023)
This study aims to discuss the mechanism of political dynasty working on the Benyamin-Pilar pair in the 2020 South Tangerang City Local Leaders Election, as a form of political dynasty practice in the 2020 South Tangerang City Local Leaders Election. The method used in this study is descriptive qualitative using primary data sources and secondary data. The sampling technique was carried out by purposive sampling. Researchers used four stages of data analysis according to Miles & Huberman, namely data collection, data reduction, data presentation, and withdrawal/verification with data triangulation. The final results of this study indicate that the mechanism of the political dynasty works for the Benyamin-Pilar pair in the 2020 South Tangerang City Local Leaders Election through the modalities owned by the Political Dynasty. The modality owned by the political dynasty of Ratu Atut Chosiyah is one of the factors that influences the power possessed by Benyamin Davnie and Pilar Saga Ichsan in the 2020 South Tangerang City Local Leaders Election. The political dynasty of Ratu Atut Chosiyah works through its five capitals, namely social capital, economic capital, cultural capital, symbolic capital, and political capital. The five capitals work in different forms. In social capital, Ratu Atut Chosiyah's political dynasty worked by inheriting a mass base. In terms of economic capital, Ratu Atut Chosiyah's political dynasty works through a family economic cartel. In terms of cultural capital, Ratu Atut Chosiyah's political dynasty worked by making people's culture, education and achievements a means of power reproduction. In the symbolic capital, Ratu Atut Chosiyah's political dynasty worked to be realized by inheriting symbolic power. On political capital, Ratu Atut Chosiyah's political dynasty worked by influencing the support of political parties. The drawback of this research is that the scope of the discussion only discusses the mechanism of political dynasties working based on the modality aspect they have. So this can be a reference for further research to discuss in other aspects. Keywords: Politics Dynasties, Local Elections, Tangerang Selatan City